2012
DOI: 10.1016/j.foodres.2011.12.009
|View full text |Cite
|
Sign up to set email alerts
|

Fruiting body, spores and in vitro produced mycelium of Ganoderma lucidum from Northeast Portugal: A comparative study of the antioxidant potential of phenolic and polysaccharidic extracts

Abstract: Abbreviations CATCatalase DAD Diode array detector DPPH 2,2-Diphenyl-1-picrylhydrazyl EC 50Extract concentration providing 50% antioxidant activity or 0.5 absorbance in the reducing power assay FB Fruiting body GAE Gallic acid equivalents GPx Glutathione peroxidase GSH Reduced glutathioneHPLC High-performance liquid chromatography IS Internal standard M Mycelium MMN Melin-Norkans medium MS Mass spectrometry PDA Potato dextrose agar medium PE Polysaccharides equivalents Ph Phenolic extract Ps Polysaccharidic ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
112
6

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 138 publications
(128 citation statements)
references
References 29 publications
10
112
6
Order By: Relevance
“…The antioxidant activity of crude polysaccharidic extracts obtained from Ganoderma sp., have been recently described (Shi et al, 2010;Yang et al, 2010;Heleno et al, 2012;Kozarski et al, 2012;Zhao et al, 2012;Pan et al, 2013).…”
Section: Crude Polysaccharidic Ganoderma Extractsmentioning
confidence: 96%
See 2 more Smart Citations
“…The antioxidant activity of crude polysaccharidic extracts obtained from Ganoderma sp., have been recently described (Shi et al, 2010;Yang et al, 2010;Heleno et al, 2012;Kozarski et al, 2012;Zhao et al, 2012;Pan et al, 2013).…”
Section: Crude Polysaccharidic Ganoderma Extractsmentioning
confidence: 96%
“…The above mentioned genus has been widely studied regarding its bioactive properties (Paterson, 2006;Nie et al, 2013), including antibacterial, antioxidant, antitumor and other effects (Wang et al, 1997;Wasser, 2002;Heleno et al, 2012;Li et al, 2012;Heleno et al, 2013;Popović et al, 2013;Zhonghui et al, 2013). The beneficial health properties of Ganoderma species are attributed to a wide variety of bioactive components, such as polysaccharides, triterpenes, sterols, lectins and other proteins Ferreira et al, 2010).…”
Section: Bioactivity Of Ganodermamentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, Yildiz et al (2015) have also detected the presence of syringic acid in the methanolic extracts from this matrix, which is consistent with results achieved in this work. Heleno et al (2012) and Stojkovic et al (2014) also reported the presence of p-coumaric and cinnamic acids in the fruiting body of G. lucidum, but differences in the extraction procedure, and used environment for mushroom maturation can justify the dissimilarity found in the achieved phenolic composition and other secondary metabolites profiles.…”
Section: G Lucidum Ethanolic Extracts As Relevant Bioactive Extractsmentioning
confidence: 99%
“…The phenolic composition of G. lucidum has also been widely studied and phenolic acids represent the most prominent class including chlorogenic, cinnamic, gallic, protocatechuic, p-hydroxybenzoic and p-coumaric acids. These molecules have been identified as contributors to its antioxidant, antimicrobial, antityrosinase and anti-inflammatory properties (Heleno et al, 2013(Heleno et al, , 2012Min-Young et al, 2008;Sheikh et al, 2014;Stojkovic et al, 2014). Besides all these bioactive compounds, G. lucidum nutritional composition reveals high potential to be used in the design of dietary supplements (e.g., tablets and capsules) for oral administration (Stojkovic et al, 2014).…”
Section: Introductionmentioning
confidence: 99%